Reactive power management for voltage stability of the Luzon Power Grid - Viray, Frederick M. (1998)
The increasing use of power generation outside the load center of the Luzon Power Grid has created voltage problems for which a solution must be sought. The present operational and practices are focused on the balance of the real power (MW) generation and demand in order to maintain the system frequency. The reactive power (MVAr) generation, however, is not considered to be as important as the MW generation. Although, MVAr generation is being utilized as a solution to any voltage problem which may occur, the practice is more of a reaction to the problem and not a preemptive solution which eliminates voltage problems. Computer simulations are conducted to study the voltage profile of the grid, using the set up where the source of generation is maximum outside the load center. Simulations show than an outage of generating units or lines, particularly the Extra High Voltage 500 kV line(s), can cause a system voltage collapse resulting in a system blackout. This can be largely attributed to the low voltage initial profile than the outage of a MVAr source. The low voltage profile is a result of the present practice of the System Operations of not managing MVAr. The Reactive Power Management (RPM) program which is developed in this papre defines the activities of the different groups involved in the operation of the system. The procedure, operating rules, and strategies are determined with the objective of managing the MVAr. This includes activities to be performed by System Operations Planning to the Reactive Power Dispatch and Control. An information tool is also developed to support the MVAr dispatching activity. This tool includes the capability curves of the different generating units with their corresponding limits (i.e. current and temperatures). A list of existing compensators, substations with On-Load Tap Changer, and a summary of the effect of changing the MVAr at specific nodes is also an added feature in this tool. Utilizing the developed RPM program, computer simulations show that the voltage at the different nodes of the system can be maintained within the nominal level. The margins between the operating point to the point of system collapse is significantly increased. A reduction in the system losses is also achieved. The program prevented system collapse or divergence in the simulation where an outage of generating equipment or transmission lines occurs. Its contribution is also verified by comparing the change in voltage with respect to a change in MW load. The Voltage Collapse Proximity Indicator is used to determine where the system is operating with respect to the point of system collapse.